IMPLEMENTATION OF INTEGRATED RURAL DEVELOPMENT CONCEPT (IRD) IN DEVELOPING MUKIM OF SIDAM KANAN, KEDAH, MALAYSIA - Taufek Mohd Hanapiah; Noor Aimran Samsudin; Muhammad Farid , (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This study investigates the feasibility of an integrated economy of seven (7) villages in the Mukim of Sidam Kanan (sub-district), Kedah, Malaysia, by adopting the 'Integrated Rural Development (IRD)' to develop their economy. The concept of IRD promoted a continuous intervention and collaboration process that involved external parties such as government agencies to improve the rural local economy and quality of life. Villagers' aspiration to improve their economic wealth was blended carefully with preserving local values through local distribution, reducing incongruity between rural-urban and seeking alternatives to strengthen and use natural resources. The economic sectors intended to integrate into this mukim are agriculture, livestock, aquaculture, small and medium entrepreneurs (SME) industries and rural tourism. Therefore, the interest of this paper is to evaluate the feasibility of these economies by using Creativity Index Analysis (C.I), GAP Analysis, SWOT Analysis and Financial Analysis in determining the best practice framework. Return of investment for overall proposed projects shows 20% per cent. Moreover, the 1.0 Creativity Index values can define the economic integration potential and the disparities in this rural area that are overcome from the analysis. Most importantly, more than 70% of the 99 respondents from this area agreed with the project implementation. To ensure the feasibility of the IRD, the development framework proposed at least three potential aspects within five years need to be considered: training, new and existing development and assistance in product marketing.